Biopsychosocial Determinants of Stunting in Children Under Five: A Path Analysis Evidence from the Border Area West Kalimantan - Indriyani, Eny; Dewi, Yulia Lanti Retno; Salimo, Harsono (Journal of Maternal and Child Health, 2018)
Background: Stunting is a form of nutritional deficiency associated with delayed of children growth and development. Stunting is a lack of linear development due to long-term malnutrition. This study aimed to examine factors associated with stunting in children under-five in West Kalimantan, Indonesia.Subjects and Method: This was an analytic observational study with a case-control design. The study was conducted in West Kalimantan, Indonesia. A sample of 200 children under five consisting of 100 stunting children and 100 normal children was selected for this study by fixed disease sampling. The dependent variable was stunting. The independent variables were birth length, maternal education, family income, maternal nutritional intake, maternal middle-upper arm circumference (MUAC), child nutritional intake, and the number of children. The data were collected by questionnaire. The data were analyzed by path analysis.Results: The risk of stunting directly increased with child nutritional intake less than recommended nutritional allowance (b= 1.61; 95% CI= 0.86 to 2.36; p<0.001), birth length <48 cm (b= 2.13; 95% CI= 0.95 to 3.31; p<0.001), and low current maternal education (b= 1.96; 95% CI= 1.21 to 2.72; p<0.001). The risk of stunting was indirectly and significantly influenced by family income during gestation, the number of children, maternal height, maternal MUAC, family support, maternal education during gestation, and maternal nutrient intake during gestation.Conclusion: The risk of stunting directly increases with child nutritional intakes than recommended nutritional allowance, birth length <48 cm, and low current maternal education. The risk of stunting is indirectly and significantly influenced by family income during gestation, the number of children, maternal height, maternal MUAC, family support, maternal education during gestation, and maternal nutrient intake during gestation.Keywords: stunting, biopsikososial factors, gestationCorrespondence: Eny Indriyani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta, Central Java. Email: zubair.alhafizh@yahoo.com. Mobile:+6282158338438.Journal of Maternal and Child Health (2018), 3(2): 146-155https://doi.org/10.26911/thejmch.2018.03.02.07